2013
DOI: 10.4236/jmmce.2013.13018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatments on Corrosion of Welded Low-Carbon Steel in Acid and Salt Environments

Abstract: Effect of heat treatment on the corrosion of welded low-carbon steel in 0.3 M and 0.5 M of hydrochloric acid and sodium chloride environments at ambient temperature (25˚C) has been investigated. Arc welded low-carbon steel sample of known composition were subjected to the corrosion reagents for 21 days (504 hours). pH and weight loss values were taken at interval of 3 days. Thereafter, weight loss method was used to measure the rate of corrosion attack on the heat treated samples at ambient temperature. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…Results showed that annealed specimen with coarser grain structure exhibited better corrosion resistance over other specimens. The findings were comparable to a similar study by Siedu [17], in which the bigger the grain structure the more corrosion resistant it was. This can be explained by larger grains tends to minimize the difference in potential for galvanic cell to occur [3,4].…”
Section: Microscopy Analysissupporting
confidence: 81%
“…Results showed that annealed specimen with coarser grain structure exhibited better corrosion resistance over other specimens. The findings were comparable to a similar study by Siedu [17], in which the bigger the grain structure the more corrosion resistant it was. This can be explained by larger grains tends to minimize the difference in potential for galvanic cell to occur [3,4].…”
Section: Microscopy Analysissupporting
confidence: 81%
“…Similarly, the increase in the values of the corrosion current densities (Icorr) and corrosion potentials (Ecorr) of the weldment after post weld heat treatment increased its susceptibility to corrosion. The high Icorr and Ecorr values of the weldment of the PWHT sample could be that annealed sample may not have reasonable tolerance for corrosion in harsh environment [16].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The slight difference is an indication that the amount of rust product formed is very minimal as compared to other samples. Thus, the corrosion of the specimen in the medium was highly suppressed by the coating membrane which is also an indication of stronger adhesion of the coating to the substrate 9 .…”
Section: Resultsmentioning
confidence: 94%
“…Mathiazhagan et al 8 studied electro deposition of Ni–Cr 2 O 3 nanocomposites and showed that the application of these nanocomposites on mild steel surface improved the tribological and mechanical properties of the steel. Seidu and Kutelu 9 produced a ternary Zn–Cr 2 O 3 –SiO 2 nanocomposite coating on mild steel using electrolytic chloride bath solution and reported an improvement in tribological behaviour and better thermal stability of the nanocomposite coating. Abd et al 10 investigated the corrosion resistance of Zn–Co–TiO 2 nanocomposite and reported an improved interfacial interaction between the nanoparticles which lead to improved corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%